Prognostic value of the PaO2/FiO2 ratio determined at the end‐surgery stage of a double‐lung transplantation. Issue 5 (4th April 2019) - Fessler, Julien; Thes, Jacques; Pirracchio, Romain; Godement, Mathieu; Sage, Edouard; Roux, Antoine; Parquin, François; Cerf, Charles; Fischler, Marc; Le Guen, Morgan
Abstract: Introduction: We evaluated the prognostic role of the arterial oxygen partial pressure/fractional inspired oxygen ratio (PaO2 /FiO2 ratio) measured at the end of double‐lung transplantation (DLT). Methods: This was a monocentric cohort study of all consecutive DLT patients between January 1, 2012, and January 1, 2016, except patients with preoperative extracorporeal membrane oxygenation (ECMO), intraoperative cardiopulmonary bypass, postoperative ECMO, large patent foramen ovale, redo transplantation during the study period, and multiorgan transplantation. Results: A total of 164 patients were included in the study; 45 had a PaO2 /FiO2 ratio <200, 39 a ratio in the range 200‐300, and 80 a ratio >300. The risk of being in the lower ratio group is positively related to body mass index, preoperative pulmonary hypertension, and fibrosis. It is negatively related to emergency surgery, age, and intraoperative institution of ECMO. There was a trend for more grade 3 pulmonary graft dysfunction at day 3 in the worst PaO2 /FiO2 ratio group. Mortality at 1000 days was similar for all patients and even after exclusion of patients who had required intraoperative ECMO. Conclusion: PaO2 /FiO2 ratio measured at the end of DLT does not forecast 1000‐day mortality.